Exquisite skeletons of a new transitional plesiosaur fill gap in the evolutionary history of plesiosauroids - Sachs, Sven; Eggmaier, Stefan; Madzia, Daniel (Frontiers in Earth Science, 2024)
Plesiosaurs are Mesozoic reptiles fully adapted to an aquatic lifestyle. Throughout their evolutionary history exceeding 140 million years plesiosaurs dispersed globally, achieved substantial diversity, occupied a variety of ecological niches, and experienced multiple faunal turnovers. Of those, the Early/Middle Jurassic transition event (~175–171 Mya) has recently became of increased interest because it apparently profoundly affected all three major lineages of plesiosaurs. Once dominant Rhomaleosauridae started to vanish, while Pliosauridae and Plesiosauroidea diversified and gave rise to several clades that flourished for tens of millions of years. Here, we report exquisite, three-dimensionally preserved skeletons of a new plesiosaur from the Lower Jurassic of Germany. Franconiasaurus brevispinus gen. et sp. nov. lived during the late Toarcian (~175 Mya), near the onset of the Early–Middle Jurassic turnover. Franconiasaurus displays an intriguing mixture of features, combining characters almost uniformly distributed among early plesiosaurs with those typically observed in later-diverging members of the clade. Phylogenetic analyses firmly place Franconiasaurus as the sister taxon to Cryptoclidia, bridging an evolutionary gap between early plesiosauroids, such as Plesiosaurus-like forms and microcleidids, and later-diverging representatives of the clade, such as cryptoclidids, leptocleidians, and elasmosaurids.